Panorama the new killing fields - Kemp, Darren (Australia : BBC Active, 2006)
Panorama travels to Darfur to investigate the murder, massacre and rape and ask whether the killing constitude genocide, and if so what responsibilities does that give international community to intervene. Searching out the leaders of the Jenjaweed, the programme also asks whether the killers have been taking their orders from the Sudanese government
Title from title screen
Editor, Mike Robinson ; camera, Fred Scott
Reporter: Hilary Anderson
DVD Format
Keywords: Genocide -- Darfur; Crimes against humanity; Ethnic relations -- Political aspects